Desempenho agronômico e ensilabilidade de genótipos de sorgo de diferentes propósitos cultivados em primeira safra no Norte de Mato Grosso - Rosa, Maria Antonia Bortolucci da (2021)
The demand for sorghum cultivars of better quality and productivity stimulates the emergence of numerous genotypes with specific characteristics of size, cycle, and aptitude, which have a marked influence on the productivity and nutritional value of the silage produced. In this scenario, the objective was to evaluate the agronomic performance and ensilability of experimental and commercial sorghum cultivars of different aptitudes. The experiment was conducted at Embrapa Agrossilvipastoril and at UFMT in Sinop/MT. Different genotypes were evaluated focusing on characteristics such as height, production, physical proportions of plants and intrinsic factors that may influence the silage fermentation process, such as buffering capacity, soluble carbohydrates, dry matter, fermentation coefficient and forage bromatological characteristics. Thus, eight experimental hybrids from Embrapa (forages 15F30005 and 15F30006, saccharine CMSXS 5027, 5030, 5043 and 5045 and biomass 2019B008 and CMSXS 7501 bmr) and seven commercial hybrids (forages BRS 658, BRS 659, Volumax, BRS Ponta Negra, saccharine BRS 511, and biomass BRS 716 and AGRI-002E) in a randomized block design, with 15 treatments and three replications. Data were grouped and evaluated by the method proposed by Scott-Knott (P<0.05), showing differences between genotypes for all variables, except for plant population. The group with the earliest flowering was composed of BRS 659 and BRS 511, with 70 and 69 days, respectively, and as a later one, CMSXS 7501 bmr, with 136 days. Regarding plant height, the group consisting of 2019B008, BRS 716 and AGRI-002E was considered taller, with an average of 5.27 m. For leaves, the cultivar Volumax, with 202.1 g kg-1 DM, stood out, for stem, the group with the highest proportion, constituted by BRS 511, CMSXS 5043, CMSXS 5045, AGRI-002E, BRS 716, CMSXS 7501 and 2019B008, with an average of 797.9 g kg-1 MS. For panicle, four groups were generated, with BRS 658 and BRS 659 with the highest proportion, 397.8 g kg-1 DM. The highest yields in green matter belonged to the group formed by BRS 716 and CMSXS 5043, with an average of 101.9 Mg ha-1 . For dry matter production, cultivars AGRI-002E and BRS 716 formed the group with the highest average, with 28.77 Mg ha-1 . The BRS 716, AGRI-002E, BRS 658 and 659 had higher dry matter contents, with 297.7 g kg-1 DM. For buffer capacity, BRS 511 had the lowest content, of 16.2 g kg-1 DM. For soluble carbohydrates, BRS 511 and CMSXS 5030 had the highest average, 391.7 g kg-1 DM. Among the bromatological characteristics, the materials CMSXS 5043, 5045, AGRI-002E, BRS 716 and 2019B008 stand out with the highest average for insoluble fiber in neutral detergent corrected for ash and protein, with 687.4 g kg-1 MS. For crude protein, BRS 658 and 659 stand out with the highest average, 70.9 g kg-1 DM. For non-fibrous carbohydrates, the highest contents were in the group composed of BRS 511, CMSXS 5027 and 5030, with 443.2 g kg-1 DM on average. For total digestible nutrients, the group with the highest average, with 639.31 g kg-1 of DM, was composed of saccharine BRS 511, CMSXS 5027 and CMSXS 5030. All genotypes proved to be able to be ensiled and produce silages with an adequate fermentation pattern.